Pengembangan Modul Terintegrasi Keislaman Materi Sistem Reproduksi Kelas IX SMPN 4 Katingan Kuala - Dewi Haryanti; Nurul Septiana; Nanik Lestariningsih (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study aims to produce an Islamic learning module integrated with reproductive system material that has valid, practical and effective criteria so that the module can be used in learning and can improve student learning outcomes. This research uses the Research & Development method and is developed using the ADDIE model with Analyze stages, namely requirements analysis, Design which is the design / draft module, Development which is product development based on material validation, design validation, Islamic validation, small-scale trials, module revisions, Implementation ie the application of modules in large-scale trials of experimental classes (learning using modules), Evaluate is the final module. The results of this study indicate that the modules developed are suitable for use in learning science reproductive system material obtained from the validity value of the material experts obtained from the value of 86.03% with valid criteria, design experts 82.44% valid, Islamic experts 85.52% valid. The practicality of using modules was obtained from observations of learning accomplishments of 98.65% with very successful criteria and the questionnaire responses of students showed a value with a percentage of 91.47% with the practical module category used. The effectiveness of the use of modules is obtained from an increase in student learning outcomes with N-Gain of 0.82 in the high category compared to the control class of an N-Gain value of 0.29 with a low category. Thus, the learning modules developed are valid, practical, and effective for use in learning.Keywords: Development; Module; Islamic integration